L’installation de la Finance en France. - Benjamin Coriat (Revue de la Régulation)
The paper retraces the conditions under which Finance and financial agents were able to establish their power in the French economy. The consequences of the exercise of the new power of finance on firms behaviours, and more generally on the Industrial Organization of the French economy are underlined.The main thesis is that because of the massive privatizations – relayed by a series of new regulations implemented in the last three decades- France has lost the traditional mode of coordination between agents which characterized the fordist era. This mode of coordination based on actions and initiatives undertaken by the visible hand of the public authorities, especially in the field of industrial policy, has now lost its grounds.